Pemetaan Zona Potensi Penangkapan Ikan Tongkol (Euthynnus Affinis) di Perairan Selat Makassar Sulawesi Barat - Fitri Indah Yani Fitri; Warda Susaniati; Sahabuddin; Nurul Mutmainnah; Yusdalifa Ekayanti Yunus; Ummu Kaltsum SC; Rismawaty Rusdi; Muh. Kasim (Jurnal Galung Tropika, 2025)
One of the areas directly adjacent to the Makassar Strait is the city of Mamuju, which is a potential area for tuna (Euthynnus affinis) fishing. This study aimed to analyze the spatial and temporal mapping of tuna ZPPI based on remote sensing GIS technology for fisheries in the Makassar Strait waters, West Sulawesi. The research method used in-situ data: fishing position, catch results, and oceanographic dynamics. Ex-situ data used monthly image data of sea surface temperature (SST), chlorophyll-a (aqua modis). The data was processed using multiple regression analysis between catch results and several oceanographic parameters. The results were then visualized as a map with a Geographic Information System (GIS) using ArcView 10.2 software to obtain potential tuna fishing areas in the Makassar Strait. The results showed a strong correlation between SST and chlorophyll-a with catch results, which was 83.5%. In addition, temporal time data for fishing was obtained in March, April, May, and June. The coordinates of the fishing area points for March are 118o50'12” and 2O 45'5”; in April, they are at 118O 23'15” and 2O30'4”; in May, they are at 118o 23'0” and 2 o30’4”; and in June they are at 118 o23’0” and 2 o28’0”. The Fishing Potential Zone (ZPPI) for tuna is at 118 o27’ and 2 o29’ 32” to 118 o16’ 48” and 2 o16’ 48”.